PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PADA KOPERASI SEKECAMATAN ABIANSEMAL - Ni Kadek Dinda Loveli; Putu Cita Ayu; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2022)
The objective to determine internal control system and HR competence on financial reports at the Abiansemal Distrik Cooperative, which consists of savings and loan cooperatives and multi-business cooperatives. The population were all employes of the Abiansemal Sub-district Cooperative, as many as 489 employees. The sample used was 199 employees of the Abiansemal District Cooperative. The sampling technique is purposive sampling, sampling with consideration. Analys used multiple liniar regresion analysi. The results of the analysis show that the internal control system and human resource competence have effect on the quality of financial reports at the Abiansemal Sub-district Cooperative.